2022
DOI: 10.1155/2022/9550499
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of circRNAs in Intervertebral Disc Degeneration: Inflammation, Extracellular Matrix Metabolism, and Apoptosis

Abstract: Low back pain (LBP) is seriously harmful to human health and produces heavy economic burden. And most scholars hold that intervertebral disc degeneration (IDD) is the primary cause of LBP. With the study of IDD, aberrant expression of gene has become an important pathogenic factor of IDD. Circular RNAs (circRNAs), as a kind of noncoding RNA (ncRNA), participate in the regulation of genetic transcription and translation and further affect the expression of inflammatory cytokine, metabolism of extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 106 publications
5
19
0
1
Order By: Relevance
“…Однако в некоторых кольцевых РНК третья позиция более консервативна, чем в экзонах (которые не входят в состав кольцевой РНК), что позволяет предположить, что эти высокостабильные кольцевые РНК обладают значительными некодирующими функциями. Кольцевые РНК могут действовать как посттранскрипционные регуляторы, конкурируя за связывание с микроРНК и РСБ с другими видами РНК [197,198]. Если функциональная классификация в целом выполняется в соответствии с мишенью кольцевой РНК, то их, как правило, можно разделить на две категории: регулирующие сайт-мишень и регулирующие его ген.…”
Section: научные обзорыunclassified
“…Однако в некоторых кольцевых РНК третья позиция более консервативна, чем в экзонах (которые не входят в состав кольцевой РНК), что позволяет предположить, что эти высокостабильные кольцевые РНК обладают значительными некодирующими функциями. Кольцевые РНК могут действовать как посттранскрипционные регуляторы, конкурируя за связывание с микроРНК и РСБ с другими видами РНК [197,198]. Если функциональная классификация в целом выполняется в соответствии с мишенью кольцевой РНК, то их, как правило, можно разделить на две категории: регулирующие сайт-мишень и регулирующие его ген.…”
Section: научные обзорыunclassified
“…Degenerated IDs exhibit higher rates of apoptosis, but the underlying mechanisms remain unclear ( 55 ). Importantly, evidence indicates that ncRNAs are involved in abnormal apoptosis of NP cells during IDD ( 56 ). It is reported that numerous ncRNAs can simultaneously affect the process of apoptosis and autophagy during development of IDD ( 57 , 58 ).…”
Section: Ncrnas In Autophagy and Apoptosismentioning
confidence: 99%
“…ncRNA includes short hairpin RNA (shRNA), small interfering RNA (siRNA), antisense RNA, microRNA (miRNA), long non-coding RNA (lncRNA), circular RNA (circRNA), and extracellular RNA [ 260 , 261 , 262 ]. Although evidence suggests that miRNA, lncRNA, and circRNA contribute to the progression of IVDD by affecting the processes of apoptosis, cell proliferation, ECM degradation, and inflammation [ 263 , 264 , 265 , 266 ], the role of ncRNA in autophagy is unclear. Figure 4 depicts autophagy-targeting ncRNAs that can be exploited to treat IVDD.…”
Section: Autophagy As a Potential Therapeutic Target For Ivddmentioning
confidence: 99%
“…circRNA regulates gene transcription and translation as well as inflammatory cytokine release, ECM metabolism, and cell proliferation and death [ 266 ], suggesting that it could be therapeutically targeted in IVDD. However, our understanding of the mechanism by which circRNA impacts IVDD is still limited.…”
Section: Autophagy As a Potential Therapeutic Target For Ivddmentioning
confidence: 99%
See 1 more Smart Citation